Applying a Risk Management Approach in Controlling QMS Processes and Interactions with the Relevant Interested Parties: The Case of an Airport - Belmir Fouzi; Hanae El Idrissi; Jebbour Nouzha (Iraqi Journal of Science, 2021)
Fes Airport, run by the National Airports‟ Office in Morocco, aspires to be certified by the ISO 9001: 2015 standard; Hereby, it has to meet the needs of the stakeholders‟ expectations in an attempt to promote the airport activities, it has also to take into consideration the risks that are related to the various actors who have well-set priorities and expectations.The aim of this article is to shed light on the interconnection between the various participants in an attempts to meet the new requirement 4.2 of the ISO 9001: 2015 and to examine the dangers of the integrated management system (QSE) taking into consideration the proposal of an action plan to monitor interfaces, and to promote the application of an integrated approach, in collaboration with concerned participants as well as the amelioration of an integrated management system to realize the various goals set by the different participants and satisfy the passengers.